Cinematic London: Brexit and symbolic power (Altre Modernità, 2018)
In this paper, I examine the ways in which London’s symbolic power and, correlatively, its cinematic image, are evolving in the post-European Union referendum era. This paper identifies the ways in which the possible changes in London’s material and cinematic image as a dynamic, opening and welcoming city are beginning to manifest themselves in mainstream cinema and cinema-inspired advertising. In particular, I provide an assessment of the current state of the British film industry, highlighting the ways in which EU-funded programmes, like Creative Europe, provide filmmakers in the UK with access to funds and potentially wide distribution. I then discuss the impact the Brexit decision has had on London-based films released after the referendum. Finally, I provide a sociological-thematic analysis, influenced by discourse analysis and semiotic analysis, of two film-themed advertisements (London is the City of Film and Nothing Beats a Londoner), demonstrating the ways in which the uncertainly following the EU referendum is manifested on screen. Ultimately, this paper provides an Saggi/Ensayos/Essais/Essays N. 20 – 11/2018 157 insight into the ways in which London’s material and cinematic identities are evolving as the city and indeed the rest of the UK re-evaluate their place on the global stage.